Effect of permeability on the initiation of Atherosclerosis modeled as an inflammatory process. (7th May 2023) - El Hajj, W.; El Khatib, N.
Abstract: This work presents a mathematical model, based on partial differential equations, that analyzes the inflammatory stage of atherosclerosis. Four leading players are taken into consideration: Low Density Lipoproteins, oxidized Low Density Lipoproteins, immune cells and the inflammatory cytokines. In addition to this, the permeability of the endothelial layer is taken into account in the model. A stability analysis of the fixed points of the kinetic system is presented in details followed by the proof of existence of traveling wave solutions of the system of partial differential equations. The mathematical analysis leads to a biological interpretation. We distinguish three main cases of the disease state that correlate with the permeability of the endothelial layer. In fact, having a low permeability indicates the disease free state since no chronic inflammatory reaction occurs due to the non initiation of the inflammation. With intermediate permeability, a wave propagation corresponding to a chronic inflammatory reaction might occur whether the initial perturbation overcomes a threshold or not. With high permeability, even a small perturbation of the disease free state leads to a chronic inflammatory reaction represented by a wave propagation. We perform numerical simulations of the solutions to illustrate the biological results. Highlights: We develop a mathematical model for the initiation of atherosclerosis The model is based on PDE of reaction–diffusion type. We characterize the different inflammation stages. We incorporate the permeability of the endothelial layer. The progress of the inflammation is described as a traveling wave. We setup a map that determines the inflammation setup in terms of the permeability.